Entecavir safety and effectiveness in a national cohort of treatment‐naïve chronic hepatitis B patients in the US – the ENUMERATE study. Issue 1 (28th October 2015) - Ahn, J.; Lee, H. M.; Lim, J. K.; Pan, C. Q.; Nguyen, M. H.; Ray Kim, W.; Mannalithara, A.; Trinh, H.; Chu, D.; Tran, T.; Min, A.; Do, S.; et al.
Summary: Background: Entecavir (ETV) has been shown to be safe and efficacious in randomised controlled trials in highly selected patients with hepatitis B virus (HBV) infection. Aim: To determine the safety and effectiveness of ETV in 'real‐world' HBV patients in the United States (US). Methods: Treatment‐naïve HBV patients ≥18 years old who received ETV for ≥12 months between 2005 and 2013 were included in a retrospective, cohort study. Rates of ALT normalisation, undetectable HBV DNA, HBeAg and HBsAg loss/seroconversion, adverse events (AE) and clinical outcomes were evaluated. Results: Of 841 patients, 658 [65% male, 83% Asian; median age 47 years] met the inclusion criteria. 36% were HBeAg+ and 9.3% cirrhotic. 89% had abnormal ALT. Baseline median HBV DNA was 5.8 log 10 IU/mL. Median duration of ETV treatment was 4 years. Rates of ALT normalisation at 1, 3 and 5 years were 37.2%, 48.7% and 56.2% in HBeAg+ and 39.6%, 46.8% and 55.6% in HBeAg‐ patients. HBV DNA was undetectable at 1, 3 and 5 years in 34.6%, 64.7% and 84.6% in HBeAg+ patients, and 81.9%, 90.3% and 96.2% in HBeAg patients. Five‐year cumulative probability of HBeAg loss and seroconversion was 46% and 33.7% and HBsAg loss was 4.6%. ETV was discontinued due to adverse events in 1.2% of patients. Hepatic decompensation occurred in 0.8%, liver cancer in 2.7% and death in 0.6%. Conclusion: Entecavir treatment was safe in a large cohort of US patients, but ALT normalisation and hepatitis B virus DNA suppression rates were lower than previously reported in clinical trials.